ChemInform Abstract: Aqueous Copper Nitrate Catalyzed Synthesis of 3‐Alkylideneoxindoles from α‐Diazo‐β‐ketoanilides. Issue 8 (February 2015) - Mo, Shanyan; Yang, Zhanhui; Xu, Jiaxi
Abstract The title reaction allows the cyclization of a variety of N‐arylated α‐diazo‐β‐keto amides to indoles in moderate to excellent yields.